Detecção de papilomavírus humanos pela técnica de captura híbridas: study preliminary - Carvalho, Maria O.O.; Almeida, Ricardo W.; Leite, Fátima M.S.; Fellows, Ilza B.; Teixeira, Mariza H.; Cavalcanti, Sílvia M.B. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
ln the present study, we determined the prevalence of HPV infection by using the Hybrid Capture Test in 217 patients attending at private clinic Laboratory of the Rio de Janeiro. Among them, 184 were female and 96 out of them were infected by HPV, with 83.3% (80 patients) being positive for high risk HPVs, and hence constituting a risk group for malignant transformation. We had the opportunity of study 18 lesions for 12 to 48 months. From them, 8 were regressive lesions, 7 were peristent, 1 progressed to carcinoma, 1 were a latent infection and, finally, 1 were a transient infection a process recently detected for HPV infections. The aim of our study was to point out patients infected by high risk HPVs and thus recognise the group at a higher risk of malignant evolution, since their early detection can be essential to preveni the transformation event.